Evaluation of the Effects of Systemic Irisin Hormone Application on Osseointegration of Titanium Implants: An Experimental Study - Bulmus, Ozgur; Dundar, Serkan; Bozoglan, Alihan; Canpolat, Sinan (Lippincott Williams & Wilkins, 2022)
This study aimed to conduct a biomechanical investigation of the effects of systemic irisin hormone application on the osseointegration of titanium implants in rat tibias. After surgical implementation of titanium implants in the metaphyseal part of the tibiae of rats, the rats were randomly divided into 2 equal groups: control group (n = 10) and irisin group (n = 10). After surgery in the control group, the rats received no further treatment during the 4-week experimental period. The rats in the irisin group were given 100 ng/kg irisin every day for the 4-week experimental period after surgery. At the end of the experimental period, the rats were euthanized. implants and surrounding bone tissues were collected for biomechanical (Newton) bone implant connection analysis. The Student t test was used for statistical analysis. There were no significant differences in the biomechanical osseointeration values (Newton) of the groups (P > 0.05, P = 0.59). Also, in the irisin group, there was numerically but not statistically more bone implant connection than in the controls. Within the limitations of this study, irisin did not affect the osseointegration of titanium implants.
Keywords: Bone implant connection; dental implants; irisin hormone; osseointegration; rat tibia